Analisis Dampak Kenaikan Harga Bbm Nonsubsidi Terhadap Daya Beli Masyarakat Dan Stabilitas Ekonomi Di Kecamatan Sukajadi, Kota Pekanbaru, Riau - Fahrul Ichsan Syafa’at; Sufian Hamim (Journal of Innovative and Creativity (Joecy), 2026)
The increase in the price of non-subsidized fuel (Bahan Bakar Minyak or BBM) is a government policy that has significant implications for the socio-economic conditions of society, particularly in terms of purchasing power and economic stability. This study aims to analyze the impact of rising non-subsidized fuel prices on community purchasing power and economic stability in Sukajadi District, Pekanbaru City, Riau Province. The study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation, while informants were selected using a purposive sampling technique. Data analysis followed the model proposed by Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings indicate that the increase in non-subsidized fuel prices has led to higher transportation and operational costs, affecting household purchasing power and local economic activities. In response, the community adopted several adaptation strategies, including reducing non-essential expenditures, improving transportation efficiency, and seeking additional sources of income. Meanwhile, the government sought to maintain economic stability through inflation control measures, monitoring the prices of essential goods, and implementing social protection programs. The study concludes that rising non-subsidized fuel prices have significant effects on the local economy, highlighting the need for collaboration between the government and the community to mitigate adverse impacts and maintain regional economic stability.